PENERAPAN MODEL KNOW WANT TO KNOW LEARNED (KWL) BERBASIS VIDEO ANIMASI UNTUK MENINGKATKAN PEMAHAMAN MEMBACA TEKS CERITA PADA SISWA KELAS V UPTD SD NEGERI 13 JANGKA - Linda; Nurlaili (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low reading comprehension of story texts among fifth-grade students at UPTD SD Negeri 13 Jangka, caused by less engaging learning methods and low reading interest. This study aims to determine the improvement of reading comprehension of story texts, teacher and student activities, and student responses to the implementation of the Know Want to Know Learned (KWL) model based on animated video. This research is a Classroom Action Research (CAR) conducted in two cycles with 28 fifth-grade students as subjects. Data were collected through tests, observation sheets, and questionnaires, and analyzed descriptively and quantitatively using percentage formulas. The results show that classical completeness increased from 68% in cycle I to 93% in cycle II. Teacher and student activities each increased from 96.47% in cycle I to 98.82% in cycle II, classified as excellent. Student responses were also very positive: 74% of students strongly agreed and 25% agreed that the KWL model made it easier to understand story texts, that the animated videos clarified the story content, that group discussion facilitated comprehension, and that the learning became more enjoyable and engaging. Therefore, it can be concluded that the implementation of the KWL model based on animated video effectively improves the reading comprehension of story texts among fifth-grade students at UPTD SD Negeri 13 Jangka